Polemik dan Diskriminasi: Keterlibatan Anak dalam Penyalahgunaan Narkoba - Henky Fernando; Hasse Jubba; Yuniar Galuh Larasati; Syahrul Akmal Latif (Jurnal Community, 2022)
This study aims to describe the polemics and discrimination experienced by minors in their involvement in distributing and consuming drugs in Indonesia. This study uses a qualitative descriptive method with literature study data collection techniques by searching for relevant literature through online news pages on the internet using the search keyword "Keterlibatan anak di bawah umur dalam penyalahgunaan narkoba di Indonesia". Analysis of the data was carried out by reading and interpreting the data to describe and explain the involvement of minors in drug abuse in Indonesia without bringing irrelevant elements or assumptions. The findings of this study show that the polemic of children's involvement in drug abuse appears in determining the status of children as perpetrators or victims of drug crimes. The polemic also led to the emergence of discriminatory treatment of children from government and community institutions, such as dismissal from school, negative stigma, exclusion, and expulsion from their environment.